Self-training on specialised interpreting : an analysis of a mock consecutive interpreting of lectures on genetics - He, Mengting (Nanyang Technological University, 2021)
Specialised interpreting involves specialised topics in different disciplines such as biology, psychology, physics, etc. Specialised interpreting is needed in many industries. However, it is difficult for interpreters, especially interpreter trainees since disciplinary knowledge and a good command of terminologies are required. This project is a mock interpreting of recordings of lectures on genetics done by the investigator to explore possibilities of having interpreter trainees to develop into specialised interpreters. Based on the detailed analysis of the investigator’s output, the objective of this project is to provide interpreters, especially trainees, with suggestions on how to prepare for the interpreting of specialised discourses. Issues identified in the interpreting output caused by content that requires specialised knowledge, the speed of the speaker that caused challenges for the interpreter, and the settings of the lecturer are discussed in the project.